Apa Saja Penyebab Pengangguran di Jawa Barat? - Airlangga Surya Kusuma; Erina Putri Irwanti; Zihane Ardhanita Diaz; Kareena Putri Pelawi; Nadya Lutfiani Putri; Indika Wulandari (Veteran Economics, Management, & Accounting Review, 2025)
This study analyzes the influence of the Human Development Index (HDI), average years of schooling, and labor force participation rate (LFPR) on the open unemployment rate in West Java Province, using panel data from 15 regencies/cities. The results indicate that the Human Development Index (HDI) and average years of schooling do not have a significant effect on open unemployment, possibly due to a mismatch between workers' skills and labor market needs. In contrast, the labor force participation rate has a significant impact, where an increase in participation without adequate job creation leads to a rise in open unemployment. These findings provide important insights for the formulation of employment and education policies in West Java. Keywords: Human Development Index, Average Years of Schooling, Labor Force Participation Rate, Unemployment Rate, Regional Unemployment     Abstrak Penelitian ini untuk menganalisis pengaruh Indeks Pembangunan Manusia (IPM), rata-rata lama sekolah, dan tingkat partisipasi angkatan kerja (TPAK) terhadap tingkat pengangguran terbuka di Provinsi Jawa Barat menggunakan data panel dari 15 kabupaten/kota. Hasil analisis menunjukkan bahwa IPM dan lama sekolah tidak berpengaruh signifikan terhadap pengangguran terbuka, kemungkinan karena ketidaksesuaian antara keterampilan tenaga kerja dengan kebutuhan pasar. Sebaliknya, tingkat partisipasi angkatan kerja memiliki pengaruh signifikan, dimana peningkatan partisipasi tanpa diimbangi penciptaan lapangan kerja yang memadai menyebabkan kenaikan pengangguran terbuka. Temuan ini memberikan masukan penting bagi perumusan kebijakan ketenagakerjaan dan pendidikan di Jawa Barat.   Kata Kunci: Indeks Pembangunan Manusia, Rata-rata Lama Sekolah, Tingkat Partisipasi Angkatan Kerja, Tingkat Pengangguran, Pengangguran Regional